The subsets of blood circulating T-cells associated with the development and prognosis of coinfection in patients with critical COVID-19 - Li, Xingming; Peng, Hongqiong; Wang, Yunchuan; He, Shiying; Yang, Xueting; Chen, Jiayue (Frontiers in Immunology, 2025)
BackgroundA secondary bacterial infection, which has a high incidence in patients with critical coronavirus disease 2019 (COVID-19), has been proven to have an association with increased mortality. Adaptive immune responses have been detected in almost all COVID-19 cases. This study aimed to determine whether the levels of immune-inflammatory factors are associated with coinfection in patients with critical COVID-19.MethodsPatients with a confirmed critical severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection were enrolled in this single-center cohort study. Clinical data and venous blood samples were collected on the day of hospital admission. All patients were divided into two groups according to the presence of bacterial coinfection or absence of bacterial coinfection, which were then divided into two groups (survived group and deceased group) based on the outcome of the disease during hospitalization.ResultsPatients with coinfection had a higher mortality rate (83.3% VS 50.0%, P<0.001) and longer hospital stays (25.15 VS 13.80d, P<0.001). We observed that patients who developed coinfection tended to have a significantly lower number of CD4+ T cells (121.19 VS 207.83cells/µL, P=0.001) and CD8+ T cells (79 VS 158cells/µL, P=0.006) and a higher proportion of CD4+CD8+ double-positive T (DPT) cells (3.66% VS 1.91%, P=0.011) on the day of hospital admission. The tests for inflammatory cytokines showed a higher level of IL-4 (0.99 VS 0.42pg/mL, P<0.001) and IL-6 (109.60 VS 63.59pg/mL, P=0.009) in coinfection group. And the multivariant analyses also revealed that CD4+ cell counts < 199.5cells/µL, CD8+ cell counts < 124.5cells/µL, IL4 > 0.535pg/mL, IL6 > 388.9pg/mL could be independent risk factors for coinfection. Moreover, in the coinfection group, we observed that the deceased patients had a lower level of total lymphocytes, T cells, and albumin.ConclusionOur study found that lymphocyte subsets and cytokines play an important role in predicting bacterial coinfection in patients with critical COVID-19. Lower levels of CD4+ and CD8+ cells and higher level of IL4 and IL6 in patients on the day of admission were significantly correlated with the development of coinfection the following days in the hospital.